Francisca Gonzaga - Maestra or Maestrina? Inferences from a 19th century profession - Huguenin Botelho, Andrea (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
Considering the life and period of Franscica Gonzaga, the present article aims to investigate terminological issues about the term maestrina, as well as the vernacular erasure of maestra in Lusophone languages. Quantitative and qualitative methodologies were used with the clear intention of mapping and observing the position of maestros, maestrinos, maestras and maestrinas in nineteenth-century society. The investigative work revealed indications that these were two different musical occupations, where professionals performed similar tasks for different musical activities. Based on this assumption, it was explored the details of these two professions in the 19th century in Rio de Janeiro, in order to understand why Francisca Gonzaga was referred to as both maestra and maestrina during her life.